Impact of Co-existing Adenomyosis on Pain Recurrence Following Deep Endometriosis Excision: A Systematic Review and Meta-Analysis of Multivariate-Adjusted Observational Cohorts - Ninda Frymonalitza (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Deep endometriosis (DE) represents a severe phenotype characterized by subperitoneal infiltration >5mm. While complete surgical excision is the gold standard, postoperative recurrence of pain and lesions remains clinically significant. Growing evidence implicates co-existing adenomyosis as a prognostic factor, yet its independent impact on DE surgery outcomes is debated. Methods: We conducted a systematic review and meta-analysis of observational studies published between 2014 and 2025. Data were synthesized from seven high-quality studies involving 2,056 participants, focusing on those utilizing multivariate regression or propensity score matching. The primary outcomes were recurrence of pain (dysmenorrhea, dyspareunia), anatomical lesion recurrence, and surgical complications. Secondary outcomes included fertility. Results: The prevalence of adenomyosis in DE patients ranged from 35.6% to 49.05%. Patients with adenomyosis had significantly higher preoperative pain scores. Postoperatively, adenomyosis was an independent predictor of pain persistence and lesion recurrence. Extrinsic adenomyosis was associated with a 2.5-fold increased risk of early recurrence (OR 2.5; 95% CI 1.2–3.4). Survival analysis showed a 60% recurrence-free probability at 5 years for those with adenomyosis vs. 81% for those without. Surgical complications were significantly higher in the adenomyosis group (OR 4.56; 95% CI 1.90–11.30). Conclusion: Co-existing adenomyosis is a robust independent risk factor for failure of DE surgery, leading to persistent pain, lesion recurrence, and increased surgical morbidity. This supports the outside-in theory of pathogenesis. Preoperative screening for adenomyosis via TVS/MRI is mandatory for accurate counseling and surgical planning.